Economic Growth in Latin America - De Gregorio, Jose (IMF Working Papers; Working Paper ;, 1991)
This paper studies growth determinants in 12 Latin American countries during the period 1950-85. In a simple growth accounting framework, the share of labor in income is found to be lower in the sample group than in developed countries, while factor productivity growth accounts for a larger proportion of growth in the fastest growing countries in the sample. Using panel data, macroeconomic stability is found to play, in addition to investment (physical and human), a crucial role in growth. To a lesser extent, growth is negatively correlated with government consumption and political instability. The terms of trade appear to have no significant effect on growth.